QUALITY OF LIFE IN WOMEN ATTENDING ACADEMIES IN THE CITY OF ANÃPOLIS-GO. - Silva, Ingrid Martins da; VenÃ¢ncio, Patricia Espíndola Mota (International Journal of Movement Science and Rehabilitation, 2020)
The present research project aimed to identify the best quality of life in women attending the gym. This evaluation was made through the WHOQOL-BREF quality of life questionnaire, which contains four domains for evaluation: environmental, physical, psychological and social. The test was applied in four gyms in the city of Anápolis-GO in the year 2019. The research sample consisted of 100 participants, 20 aged between 18 and 25 years, 34 between 26 and 35 years and 46 with age above. 36 years old. As a result of this research it was evidenced that according to the psychological domain 87.5% of the older women presented better results when they demonstrated to have greater acceptance with their body image related to 45.5% of the younger participants with p = 0, 13, and regarding the physical domain, 63.0% had manifestations of better feelings such as well-being and self-esteem, as opposed to 35.7% of the young participants with p = 0.06. Thus, it was concluded that the higher the age group of individuals, the better the results related to quality of life taking into consideration physical, psychological, environmental and social aspects.